Perception of sexual abuse in intellectual disability: a literature review (Research, Society and Development, 2021)
Introduction: Intellectual disability is characterized by a below-average mental or psychosocial process, showing that they do not perform as expected, in view of their low cognitive development,a situation that can impair their perception of reality, being easy prey for the practice of abuse sexual. Objective: Describe, through studies of selected literature, situations of sexual abuse in people with intellectual disabilities, considering their ability to perceive sexuality. Signaling the fragility and vulnerability of individuals with intellectual disabilities in situations of violence. Method: This study is an Integrative Literature Review, with a qualitative and descriptive approach, elaborated through data collection in the virtual health library (VHL), in the period from 2011 to 2020, following the inclusion criteria, which were full texts and indexed in the in full, available for reading, in Portuguese, with a 10-year time frame. As an exclusion criterion, articles that were repeated or that did not comply with the proposed theme were discarded. After applying the criteria, 08 articles were selected to compose the study. Results: As results, the importance of the health professional in the approach and humanized care to the disabled patient, victim of sexual abuse and the urgency to discuss the sexuality of people with disabilities was observed. Conclusion: It is possible to conclude that people with ID need more attention from their guardians and mainly from the public power, through targeted policies thus avoiding possible sexual abuse or situations of violence.